Hillbilly elegy [compact disc, unabridged] : a memoir of a family and culture in crisis - Vance, J. D. (Harper Audio, 2016)
From a former marine and Yale Law School graduate, a powerful account of growing up in a poor Rust Belt town that offers a broader, probing look at the struggles of America's white working class.